Application Of Analytical Hierarchy Process In Choosing The Best Pawnshop: Application Of Analytical Hierarchy Process In Choosing The Best Pawnshop - Teduh Primandaru (Jurnal Mantik, 2020)
Crowded pawn shops or places have sprung up in the present. The more pawn shops appear, the fiercer the competition. In order to face competition in today's highly competitive business climate, an appropriate analysis is needed to implement reliable business strategies and policies. The Analytical Hierarchy Process is one of the most reliable methods for making the right decision in determining the best choice of mortgage